Istota wewnątrzsektorowej konsolidacji banków komercyjnych w Polsce - Swacha-Lech, Magdalena (The essence of the same-sector consolidation between the commercial banks in Poland, 2005)
The following article focuses on the problems concerning consolidation processes that are taking place within the banking sector. The essence of this phenomenon has been presented through the look at the methods of defining company consolidations, including the banks, as well as through the analysis of the factors which encourage this phenomenon, and of the basic motives for which the banks make a decision to integrate.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 51-59